2014
DOI: 10.1002/cctc.201300884
|View full text |Cite
|
Sign up to set email alerts
|

High‐Temperature Polymer Electrolyte Fuel Cell Using Poly(vinylphosphonic acid) as an Electrolyte Shows a Remarkable Durability

Abstract: The development of a high‐performance, durable, and less expensive membrane electrode assembly (MEA) composed of a polymer electrolyte membrane and electrocatalysts is important for developing fuel cells. Herein, we described the design and fabrication of an electrocatalyst with carbon black, polybenzimidazole doped with poly(vinylphosphonic acid) (PVPA), and platinum nanoparticles as an electron‐conducting support material, an electrolyte, and a metal catalyst, respectively. Most importantly, we used PVPA in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…The observed clear contrast indicated that the Nafion was immobilized on the MWNT/PyPBI/Pt surfaces based on the strong interaction through the acidebase reaction as schematically shown in Fig. 3c similar to the PVPA on the MWNT/PyPBI/Pt reported previously [27,28], while the interaction between the ox-MWNT and Nafion was not sufficiently strong to immobilize on the ox-MWNT as presented schematically in Fig. 3d.…”
Section: Resultssupporting
confidence: 54%
“…The observed clear contrast indicated that the Nafion was immobilized on the MWNT/PyPBI/Pt surfaces based on the strong interaction through the acidebase reaction as schematically shown in Fig. 3c similar to the PVPA on the MWNT/PyPBI/Pt reported previously [27,28], while the interaction between the ox-MWNT and Nafion was not sufficiently strong to immobilize on the ox-MWNT as presented schematically in Fig. 3d.…”
Section: Resultssupporting
confidence: 54%
“…Interestingly, the intensities of the N 1s and P 2p peaks of the KB/ PyPBI/Pt/PVPA were higher than those of the VC/PyPBI/Pt/ PVPA, suggesting the presence of greater amounts of the PyPBI and PVPA in the KB/PyPBI/Pt/PVPA. 43,44 The quantitative analysis of the surface elemental ratios displayed in Table 1 indicated that the P and N in the KB/PyPBI/Pt/PVPA were 2 and 3.5 times higher than those in the VC/PyPBI/Pt/PVPA, respectively, which would be due to the larger specific surface area of the KB resulting in greater amount of the PyPBI to coat the surface of the carbon. Accordingly, greater amount of the PVPA was expected to coat on the PyPBI on the KB/PyPBI/ Pt/PVPA via the acid−base reaction, which was confirmed by the TGA measurements, and the results are shown in Figure 4.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…1). In the catalyst, a thin layer of PyPBI on the MWNTs acts as an efficient anchoring layer for many different kinds of cations including Pt, Au, and Pd on pristine MWNTs2021222324252627. We report the first successful application of this strategy to metal oxides and found that uniform Ni x Co 3− x O 4 nanoparticles were homogeneously deposited on the PyPBI-wrapped MWNTs without causing any damage to the MWNTs.…”
mentioning
confidence: 95%
“…The content of N on the surface of MWNT-PyPBI was estimated to be ~2.2%. Since the thickness of the PyPBI layer is less than 1 nm, we consider that the PyPBI would not interrupt the electron transfer between catalyst and the MWNT support2021222324252627. Representative morphologies of the prepared catalysts are shown in Fig.…”
mentioning
confidence: 99%